Co-occurrence of Adult ADHD Symptoms and Problematic Internet Use and Its Links With Impulsivity, Emotion Regulation, Anxiety, and Depression - El Archi, Sarah; Barrault, Servane; Brunault, Paul; Ribadier, Aurélien; Varescon, Isabelle (Frontiers in Psychiatry, 2022)
The co-occurrence of attention-deficit/hyperactivity disorder (ADHD) and problematic Internet use (PIU) is associated with increased severity of PIU and poorer treatment outcomes. The main objective of this study was to examine the association between PIU and adult ADHD symptoms and determine whether adult ADHD symptoms were a predictor of PIU in the general adult population. We also examined the potential mediating role of the dimensional psychopathological factors, including anxiety, depression, impulsivity, and emotion regulation, in this relationship. To achieve these aims, we recruited 532 regular Internet users online from the general adult population. The participants completed an online questionnaire assessing PIU (Internet Addiction Test), anxiety and depression symptoms (Hospital Anxiety and Depression Scale), adult ADHD symptoms (Adult ADHD Self-Report Scale-V1.1), emotion regulation (Emotion Regulation Questionnaire), and impulsivity (UPPS-P Impulsive Behavior Scale). We conducted a multiple regression analysis to determine the predictors of PIU and mediation analyses to identify the psychopathological mediators of the association between adult ADHD symptoms and PIU. PIU was observed in 17.9% of our sample. A significantly higher proportion of respondents with PIU screened positive for adult ADHD symptoms compared to respondents without PIU (50.5 vs. 21.7%; p < 0.001). Individuals with PIU reported significantly higher scores than those without PIU for anxiety and depressive symptoms, impulsivity, and the emotion regulation strategy of expressive suppression. Additionally, they had significantly lower scores than those without PIU on cognitive reappraisal than non-problematic Internet users. In addition to adult ADHD symptoms, the multiple regression analysis revealed that PIU was also positively predicted by depressive symptoms, positive urgency, lack of perseverance, and expressive suppression, and is negatively predicted by cognitive reappraisal and negative urgency. The mediation analysis showed that lack of perseverance, positive urgency, and depressive and anxiety symptoms were partial mediators of the relationship between adult ADHD symptoms and PIU. Our results highlight the significant co-occurrence of PIU and adult ADHD symptoms. This study also provides support for a theoretical model in which impulsivity dimensions, emotion regulation strategies, as well as the tendency to anxiety and depressive symptoms, may play a mediating role in this co-occurrence. In summary, the findings emphasize the need to assess these psychological characteristics in problematic Internet users, as they can be a factor of clinical complexity, as well as the importance of targeting them as part of integrated interventions for both adult ADHD symptoms and PIU.